2007
DOI: 10.1007/s10389-007-0101-9
|View full text |Cite
|
Sign up to set email alerts
|

A review of European research on consumer response to nutrition information on food labels

Abstract: The aim of this study was to review research conducted in [2003][2004][2005][2006] in the EU-15 countries on how consumers perceive, understand, like and use nutrition information on food labels. Based on a search of databases on academic publications, Google-based search, and enquiries directed to a range of food retailers, food companies, consumer associations and government agencies, a total of 58 studies were identified. These studies were summarised using a standard format guided by a model of consumer in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

55
953
8
43

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 968 publications
(1,059 citation statements)
references
References 24 publications
55
953
8
43
Order By: Relevance
“…Studies investigating the role of nutrition logos in guiding buying decisions in point-of-purchase settings such as supermarkets are scarce (8,9,13,16,(18)(19)(20) . This is the first study to investigate in the supermarket the actual use of the Dutch Choices logo, a front-of-pack nutrition logo on products with a favourable product composition.…”
Section: Discussionmentioning
confidence: 99%
“…Studies investigating the role of nutrition logos in guiding buying decisions in point-of-purchase settings such as supermarkets are scarce (8,9,13,16,(18)(19)(20) . This is the first study to investigate in the supermarket the actual use of the Dutch Choices logo, a front-of-pack nutrition logo on products with a favourable product composition.…”
Section: Discussionmentioning
confidence: 99%
“…Some works showed that, compared with simple formats like health logos, detailed FOP labels (i.e. 'multiple traffic lights' and 'Guideline Daily Amounts') appear to be well accepted by consumers, probably due to more rapid and easier identification and use, along with more complete information (4,10,11) . In addition, previous studies suggested that most FOP labels are clearly understood (5)(6)(7) .…”
mentioning
confidence: 99%
“…Children, adolescents, obese older adults, individuals with less education and/or nutrition knowledge, people with lower disposable income and those with lower health awareness are less likely to use labels and/or effectively process the nutrition information presented (30)(31)(32) . Moreover, whether consumers can understand and use nutrition facts labels is contingent upon the purpose of the task (5)(6)(7)(8) . A majority appears capable to retrieve basic facts and make simple calculations/comparisons between products using numerical information on the label, but their ability and accuracy decline as the complexity of the task increases.…”
Section: Discussionmentioning
confidence: 99%
“…A long line of research documents consumers' understanding and use of nutrition facts labels, as well as their impact on dietary behaviour (5)(6)(7)(8) . A substantial proportion of US consumers report regular use of nutrition facts labels to guide their selection of food products (5)(6)(7)(8) .…”
mentioning
confidence: 99%
See 1 more Smart Citation